1998
DOI: 10.1002/(sici)1099-0895(1998090)14:3<207::aid-dmr214>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic strategies for the treatment of Type 2 diabetes

Abstract: Diabetes mellitus is the most common endocrine disease, accounting for over 200 million people affected worldwide. It is characterized by a lack of insulin secretion and/or increased cellular resistance to insulin, resulting in hyperglycemia and other metabolic disturbances. People with diabetes suffer from increased morbidity and premature mortality related to cardiovascular, microvascular and neuropathic complications. The Diabetes Control and Complication Trial (DCCT) has convincingly demonstrated the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…Their inhibition leads to a decrease in the blood glucose level since monosaccharides are the forms of carbohydrates that are readily absorbed in the small intestine (Funke & Melzig, 2006). It has been shown that an improved glycaemic control reduces diabetes related complications (Perfetti, Barnett, Mathur, & Egan, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Their inhibition leads to a decrease in the blood glucose level since monosaccharides are the forms of carbohydrates that are readily absorbed in the small intestine (Funke & Melzig, 2006). It has been shown that an improved glycaemic control reduces diabetes related complications (Perfetti, Barnett, Mathur, & Egan, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many and diverse therapeutic strategies for the treatment of Type 2 diabetes are known. Conventional treatments include the reduction of the demand for insulin, stimulation of endogenous insulin secretion, enhancement of the action of insulin at the target tissues and the inhibition of degradation of oligo-and disaccharides (Groop et al 1997, Perfetti et al 1998. One group of drugs introduced in the management of Type 2 diabetes is represented by the inhibitors of α-glucosidase.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonylurea drugs such as glibenclamide have long been used clinically to increase insulin release in type 2 diabetes (10,11). More recently, nonsulfonylurea drugs, including glinides such as nateglinide (A-4166) and mitiglinide (KAD-1229), have become available for clinical use (12)(13)(14). It is generally accepted that both sulfonylureas and glinides induce K ATP channel closure, resulting in downstream increased intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) and subsequent insulin release.…”
mentioning
confidence: 99%